Faktor-Faktor Yang Mempengaruhi Pendapatan Tradisional Di Kelurahan Manggar Baru Kota Balikpapan - Indo Rennu; Aji Sofyan Effendi; Diana Lestari (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The research entilted “Factors Affecting Income of Traditional Fishermen In New manggar village Balikpapan City”. This study aims to examine and analyze the factors that affect revenue in the traditional fishing village of new manggar town of Balikpapan.            This study uses primary data by interviewing the traditional fishing village located in a new manggar town of Balikpapan. The analysis technique used is multiple regression analysis. The results showed that the capital had no significant effect on the income of traditional fishing villages new manggar town of Balikpapan. Hours of work a significant effect on earnings in the traditional fishing village of Balikpapan city manggar new and old experience significant effect on earnings in the traditional fishing village of new manggar town of Balikpapan.